Explanation

Here, the problem is related with sequence. The sequence is already defined here. It is given by n2(n − 1).

We need to find the 8th term minus 7th term. So, our first step is to find 8th term and then to find 7th term. Using the equation of sequence, we plug n = 8 into the above equation to get the value of 8th term: 82(8 − 1) = 64(7) = 448

Using the equation of sequence, we now plug n = 7 into the above equation to get the value of 7th term: 72(7 − 1) = 49(6) = 294

Now, subtracting the value of 7th term from the value of 8th term we have: 448 − 294 = 154